Correlation between TGF-β Levels and Degree of Wound Healing in Leprosy Ulcer Patients: An Observational Study at dr. Rehatta Regional Hospital Jepara - Rizki Alfarizi; Renni Yuniati; Farmaditya Eka Putra Mundhofir; Noor Wijayahadi; Yora Nindita (Jurnal Kedokteran Diponegoro (Diponegoro Medical Journal), 2024)
Background: Ulcers are one form of chronic wounds as one form of complication experienced by leprosy sufferers. In the process of healing wounds such as ulcers, TGF-β has a broad role. Several studies have stated that in chronic wound conditions there is a decrease in TGF-β levels so that the wound is increasingly difficult to heal. This study aims to determine the relationship between TGF-β serum levels and the degree of ulcer wound healing. Methods: This study is an observational analysis study with a cross-sectional design and involved 33 leprosy ulcer patients undergoing treatment at the dr. Rehatta Jepara Hospital in the period March-April 2024. Serum TGF-β levels were measured using the Enzyme-linked immunosorbent assay (ELISA) method while the degree of wound healing was assessed by scoring the Pressure Ulcer Scale for Healing (PUSH). Bivariate analysis using the Spearman Correlation Rank Test. Results: The correlation test between serum TGF-β levels and the degree of wound healing (p = 0.807) and duration of leprosy as covariate (p = 0.96) showed insignificant results. Conclusion: There is no relationship between serum TGF-β levels and the degree of wound healing and duration of leprosy.